Morphological Evaluation of Bone Microdamage in Medication-Related Osteonecrosis of the Jaw Using Fluorescence Microscopy - Bezerra, Lilian; Carnetti , Ana Carolina Stasiak; Schulz , Riéli Elis; Silva, Heitor Fontes da; Santos , Aira Maria Bonfim; Grando , Liliane Janete; Gondak, Rogério Oliveira; Minamisako , Mariana Comparotto; Rabelo, Gustavo Davi (Journal of Oral Diagnosis, 2025)
Objective: The aim was to assess and classify bone microdamage (microcracks, microfractures, and diffuse damage) in MRONJ using fluorescence microscopy, a method that improves artefact discrimination compared to scanning electron microscopy. Methods: Patients diagnosed with MRONJ were selected, and during the surgery, bone fragments, including the sequestrum, were collected and then embedded in methylmethacrylate without decalcification. Bone microdamage was assessed in histological slides and classified as microcracks, microfracture, and diffuse damage, and bone morphology was also evaluated. Results: Ten patients were included in the study (mean age of 66.8 ± 10.4 years, five female and five male). Bone microdamage was identified in 6 patients (60%), the microcracks being the most prevalent type, followed by microfractures (20%) and diffuse damage (20%). Eroded surfaces were present in all samples, both in the cortical and cancellous bone. Other findings included the presence of amorphous non-bone material, intracortical resorption areas, and non-circular Haversian canals. Conclusion: Bone microdamage was present in more than half of MRONJ patients, and the presence of bone microcracks suggests a potential compromise in the mechanical integrity of the bone tissue.